Cardiac amyloidosis - Magdalena Balwierz; Bartosz Gruchlik; Katarzyna Mizia-Stec (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Amyloidosis is a rare disease characterized by an abnormal accumulation of the amyloid protein in tissues. Amyloidosis can be divided into two main subtypes: transthyretin amyloidosis (ATTR-CA) and immunoglobulin light chain amyloidosis (AL-CA). Accumulation of the amyloid protein in the heart muscle may lead to conduction disturbances, restrictive cardiomyopathy, and consequently, heart failure. The symptoms may include decreased exercise tolerance, shortness of breath, swelling and fainting. The diagnosis is based on laboratory tests, imaging and biopsy. Treatment focuses mainly on slowing the progression of the disease and treating the symptoms.